Abiotic and biotic responses to the 2016/2017 restoration project at the St Lucia Estuary mouth, South Africa. Issue 1 (2nd April 2020) - Jones, S; Carrasco, NK; Perissinotto, R; Fox, C
Abstract : The St Lucia Estuary is the largest estuarine lake in Africa and has been heavily impacted by anthropogenic activities, which include a history of human-induced sediment loading and separation in the 1950s of the originally common St Lucia Estuary-uMfolozi River mouth. Over the years a number of projects have been implemented aimed at countering the adverse effects that resulted from isolation of the St Lucia mouth. The most recent (2016/2017) project is the Global Environment Facility (GEF) funded initiative to restore the common St Lucia-uMfolozi River mouth. During, but especially after completion of the rehabilitation project, distinct changes in the sediment grain size composition of the estuarine substratum were observed, resulting primarily from deposition of uMfolozi River sediment in the area. Before commencement of the project (i.e. prior to June 2016) coarse and medium sediment (<1 mm >500 µm and <500 µm >250 µm, respectively) dominated. After project completion (July 2017 onwards) the substrate became muddy as a shift from coarse and medium grains to silt (<63 µm) occurred. Preliminary analyses show a corresponding shift in zooplankton and macrofauna composition. Impacts on other animals, including hippopotami and crocodiles, as well as on various flora have also been observed.